Control of Isolated Micro-Hydro Power Plant with ELC for Un-balanced Load - Basnet, Sushant; Thapa, Bharat; Kumar Tamang, Narayan; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2026)
In isolated micro-hydro power (MHP) systems, maintaining frequency and current balance under varying and unbalanced loads is essential for stable and reliable operation. Conventional Electronic Load Controllers (ELCs) regulate generator frequency by diverting excess power to dump loads; however, they activate dump loads equally across all phases, disregarding load asymmetry. This approach leads to current imbalance, zero-sequence currents, and excessive heating in the neutral conductor, which can compromise generator performance and lifespan. This paper proposes a novel phase-wise ELC control strategy that dynamically adjusts the number of dump loads in each phase independently based on real-time current measurements. By comparing each phase current with a reference full-load value, the controller ensures balanced generator operation under unbalanced consumer loads. The proposed system was modeled and simulated in MATLAB/Simulink under three scenarios: conventional ELC with balanced load, conventional ELC with unbalanced load, and the proposed ELC with unbalanced load. Simulation results show that the proposed ELC significantly reduces current imbalance, minimizes neutral current, and stabilizes rotor speed, thereby improving system efficiency and operational reliability in isolated MHP applications.